Оценка эффективности способов экстренного торможения скребкового конвейера ср72 при заклинивании рабочего органа - Ткаченко, Андрей Александрович (НТУ "ХПИ", 2010)
Various devices and ways of detection of the moment of jamming of a chain are considered. Their speed, and also efficiency of application for armored face conveyor CP72 is estimated. The comparative estimation of efficiency of ways of emergency braking of the conveyor is given at jamming with a use of Matlab model for decrease in peak tension in a chain in comparison with fluid coupling.
Estimation of efficiency of ways of emergency braking of armored face conveyor CP72 at chain jamming
Keywords: нагрузка; натяжение; гидромуфта; двигатель асинхронный; моделирование